The NOTECHS+: A Short Scale Designed for Assessing the Non-technical Skills (and more) in the Aviation and the Emergency Personnel - Ceschi, Andrea; Costantini, Arianna; Zagarese, Vivian; Avi, Eleonora; Sartori, Riccardo (Frontiers in Psychology, 2019)
This research presents the development of a short scale named “NOTECHS+” to measure the Non-Technical Skills (i.e., NOTECHS: Cooperation, Leadership and Managerial skills, Decision-Making, and Situational Awareness), Resilience and Emotion Regulation, in a sector that comprises the aviation and the emergency personnel: the Helicopter Emergency Medical Service (HEMS). The design process of the scale was carried out starting from a review on the behavioral markers used to detect the NOTECHS. Moreover, 70 interviews with HEMS experts have been conducted with the aim of developing Resilience and Emotion Regulation items by considering the different professional profiles (e.g., pilots, nurses, physicians, etc.) which compose the HEMS. Through a pre-assessment procedure, a Q-Sort test was performed on a sample of students (n = 30) to test the logical principles, but also intelligibility and clarity, of the items developed. Once the instrument was defined, 211 participants from the HEMS sector were surveyed to test the theoretical model behind the NOTECHS+ instrument. First exploratory and then confirmatory analysis yielded results that suggested that the 18 items selected conform to a bi-factor model composed of three skill-dimensions: Social skills (i.e., Cooperation, and Leadership and Managerial skills), Cognitive skills (i.e., Decision-Making and Situational Awareness) and Emotional skills (i.e., Resilience and Emotional Regulation). Finally, the study ends with a discussion on the results obtained, including practical implications on assessment and training based on this novel instrument.